La filière laine à l’heure de l’innovation sociale. Quelles transformations dans le Massif central (France)? - Jean-Baptiste Grison; Pierre-Antoine Landel (Revue de Géographie Alpine)
This article offers a comparative analysis of three socially innovative initiatives within the sheep’s wool processing sector in the Massif Central: Pôle Laine (département of Haute-Loire), Ardelaine (département of Ardèche) and Terre de Laine (département of Puy-de-Dôme). All three of these entities have successfully achieved a three-fold anchoring: anchoring within a region, anchoring within the wool processing industry and anchoring within social innovation networks. However they differ from each other in terms of the chronology of their subsequent implementation of these anchorings; being linked to the process of constructing innovative approaches, this was achieved at different stages and in a different order. But for all three centres, introducing systemic change was only possible after anchoring in all three areas had been achieved. Consequently, there is evidence that social innovation in the wool-processing industry is a response to the crisis within this weakened sector of the economy; it also serves to boost regional dynamism in struggling and land-locked mountainous areas. Lastly, we found that these three initiatives have resulted in a diversification that is not limited to the woollen industry alone; sectoral innovation has thus resulted in the emergence of full-blown regional projects.